Appropriate feeding practices and associated factors during diarrheal disease among children aged 6 to 23 months in Sub-Saharan Africa: a multilevel analysis of the recent demographic and health survey - Belayneh Shetie Workneh; Enyew Getaneh Mekonen; Alebachew Ferede Zegeye (BMC Pediatrics, 2024)
Abstract Background Diarrhea is the second leading cause of morbidity and mortality for under-five children which cause about 525,000 deaths annually. Even though diarrheal diseases have decreased substantially at the global level, low-income countries are still faced with a huge number of diarrheal diseases. Thus, our aim was to assess the child feeding practices during diarrheal diseases and associated factors among children aged 6 to 23 months in Sub-Saharan African countries using the recent demographic and health survey. Methods The appended and most recent demographic and health survey (DHS) dataset of 19 Sub-Saharan African countries from 2015 to 2020 was used for data analysis. A total of 64,628 living children aged 6–23 months with diarrhea were used as a weighted sample. The determinants of appropriate feeding practice were determined using a multilevel mixed-effects logistic regression model. Significant factors associated with appropriate feeding practice in the multilevel mixed-effect logistic regression model were declared significant at p-values < 0.05. The adjusted odds ratio (AOR) and confidence interval (CI) were used to interpret the results. Result The overall prevalence of appropriate child feeding practice during diarrhea in this study was 6.24% (95% CI: 6.06, 6.43). Maternal age (15 to 19 years and 20 to 35 years) (AOR = 1.32, 95%CI: 1.12, 1.55 and AOR = 1.14, 95%CI: 1.03, 1.27), mothers education (primary and secondary level) (AOR = 1.23, 95%CI: 1.12, 1.35 and AOR = 1.28, 95%CI: 1.15, 1.43), having media exposure(AOR = 1.36, 95%CI: 1.26, 1.46), being married (AOR = 1.18, 95%CI: 1.01, 1.38), currently working (AOR = 1.08, 95%CI:1.00, 1.15), vaccinated for Rotavirus (AOR = 1.30, 95%CI:1.19, 1.43) and living in Central and eastern African countries (AOR = 1.82, 95%CI: 1.12, 2.97) and (AOR = 2.23, 95%CI: 1.37, 3.61) respectively were significantly associated with appropriate feeding practice. Conclusion The prevalence of appropriate feeding practice during child diarrheal disease aged 6–23 months of age was strictly low which implies that child diarrhea and appropriate feeding practice is still a great issue in in Sub-Saharan African countries. Enhancing maternal education, strengthening media exposure and vaccination for rotavirus, and designing interventions that address the mother’s marital status, mother’s work status, and country category are recommended to enhance appropriate feeding practices. Furthermore, special consideration should be given to older mothers to increase appropriate feeding practices during diarrheal disease.